2016
DOI: 10.1188/16.cjon.e88-e92
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention With Transplantation Recipients to Improve Access to and Knowledge of Palliative Care

Abstract: Patient comments were positive about the successful intervention of early palliative care. The palliative care team, however, revealed a different view of the situation, showing that patients were often overwhelmed, anxious, and sometimes did not remember the content of their meetings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 5 publications
0
8
0
9
Order By: Relevance
“…3,6 Early palliative care, including ACP, involves complex interventions 7 in which professionals discuss symptom management, support end-of-life decision-making and coordinate care. Intervention trials 6,[8][9][10][11][12][13][14][15][16][17][18][19] confirm that patients with advanced cancer who receive early palliative care experience improved quality of life, 6,[19][20][21] symptoms, 6,19 and mood, 6 are more likely to document end-of-life care decisions, 19 and be knowledgeable about palliative and hospice care. 20 To provide person-centered care 22 and to involve patients in medical and future care decisions, health professionals need to understand the patient and family perspectives about their values and the impact on their care.…”
Section: Introductionmentioning
confidence: 95%
“…3,6 Early palliative care, including ACP, involves complex interventions 7 in which professionals discuss symptom management, support end-of-life decision-making and coordinate care. Intervention trials 6,[8][9][10][11][12][13][14][15][16][17][18][19] confirm that patients with advanced cancer who receive early palliative care experience improved quality of life, 6,[19][20][21] symptoms, 6,19 and mood, 6 are more likely to document end-of-life care decisions, 19 and be knowledgeable about palliative and hospice care. 20 To provide person-centered care 22 and to involve patients in medical and future care decisions, health professionals need to understand the patient and family perspectives about their values and the impact on their care.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, implementing a model of early referral to PC has also proven successful in improving the understanding of patients about PC. Evidence of this is a study that showed how 92% of patients informed and exposed to early referrals to PC felt better informed about the specialty and more eager to use their services in the future [27].…”
Section: Discussionmentioning
confidence: 97%
“…Récemment, des auteurs ont proposé d'offrir des services de soins palliatifs aux receveurs d'une GCSH parallèlement aux soins curatifs (El-Jawahri et al, 2016;Harden et Schembri, 2016;Loggers et al, 2016;Roeland et Ku, 2015;Selvaggi et al, 2014). De son côté, l'ASCO a établi des lignes directrices recommandant le recours aux soins palliatifs dans les huit semaines suivant le diagnostic lorsque les symptômes physiques ou psychosociaux sont difficiles à contrôler ou que le cancer est avancé (métastases à distance, stade avancé, pronostic de 6 à 24 mois ou cancer limitant l'espérance de vie ;Ferrell et al, 2017;Smith et al, 2012).…”
Section: Contexteunclassified